2020
DOI: 10.34133/2020/8970480
|View full text |Cite
|
Sign up to set email alerts
|

Spheroids of Endothelial Cells and Vascular Smooth Muscle Cells Promote Cell Migration in Hyaluronic Acid and Fibrinogen Composite Hydrogels

Abstract: Cell migration plays a pivotal role in many pathological and physiological processes. So far, most of the studies have been focused on 2-dimensional cell adhesion and migration. Herein, the migration behaviors of cell spheroids in 3D hydrogels obtained by polymerization of methacrylated hyaluronic acid (HA-MA) and fibrinogen (Fg) with different ratios were studied. The Fg could be released to the medium gradually along with time prolongation, achieving the dynamic change of hydrogel structures and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…We also confirmed that VSMC spheroid morphologies with DMSO are mostly spherical (Figs. 2 C, S1 C), as previously shown in other studies 35 , 36 . Inhibition of FAK phosphorylation significantly disrupted the spheroid formation of both human (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We also confirmed that VSMC spheroid morphologies with DMSO are mostly spherical (Figs. 2 C, S1 C), as previously shown in other studies 35 , 36 . Inhibition of FAK phosphorylation significantly disrupted the spheroid formation of both human (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In this study, we created VSMC spheroids , which are spherical cellular aggregates consisting of multiple layers of VSMCs 35 , 36 , using a hanging drop culture technique 37 , 38 (Fig. 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…We first confirmed that VSMC spheroid morphologies with DMSO are mostly spherical (Fig. 2C, left panel) as previously shown in other studies [33,34]. FAK activity (FAK phosphorylation at Tyr 397) in both human VSMCs ( Fig.…”
Section: Effect Of Fak Rac Rho or Cdc42 Inhibition On The Process supporting
confidence: 90%
“…In this study, therefore, to test our primary hypothesis that FAK and its downstream targets (Rac, Rho, and Cdc42) are required during the process of spheroid formation, we used VSMC spheroids as a test platform. To do this, we created VSMC spheroids in vitro, which are spherical cellular aggregates consisting of multiple layers of VSMC [33,34], using a hanging drop culture technique [35,36]. This platform can mimic a VSMC-rich neointima in the vessel wall similar to animal models that simulate human pathologies such as restenosis and atherosclerosis.…”
Section: Fak Controls Cellular Processes Including Cell Adhesion and mentioning
confidence: 99%
“…In contrast, traditional in vitro models in 2D, such as scratch/wound healing assays [26], Boyden chamber/trans-well assays [18], stencil assays [27], and tube formation assays [28] are highly controllable, but poorly represent 3D multicellular organization of angiogenesis. Some 3D models including bead assays with spheroids composed of ECs and mural cells have been used [29,30], showing 3D sprouting phenotypes, yet the model has limited imaging capacity inside the spheroids and the coverage was not fully achieved. Brudno et al employed ECs and pericytes in the bead assays and showed EC sprouting and pericyte migration with nice imaging modalities [31], yet this model barely recapitulated perfusable 3D blood vessels with functional lumens.…”
Section: Discussionmentioning
confidence: 99%